Function of marginal zone B cells in antiviral B-cell responses. - Gatto, D; Bachmann, M (2005)
B cells of the marginal zone (MZ) compartment are poised to combat infectious threats reaching the bloodstream. They owe this ability to their unique location at the ports of entry of blood-borne pathogens as well as to their distinct functional properties. MZ B cells respond to antigen encounters with rapid activation, local antibody secretion, and isotype switching. In addition, they are involved in antigen trapping, transport, and presentation. Herein, we review the current data on the functional characteristics that enable the MZ B-cell population to act as an efficient first line of defense against systemic infections.